PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, KOMPETENSI, KOMITMEN DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN (Pada CV. Tirta Indo Megah, Tumpang Malang) - Fera Dwi Apriana; Hadi Sunaryo; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTBased on research conducted with the aim of analyzing the Effect of Transformational Leadeship Style, Competence, Commitment and Communication on Employee Performance CV. Tirta Indo Megah Tumpang Malang. The population in this study were employees of CV. Tirta Indo Megah, amounting to 436 people. The sampling technique used is proportional random sampling in which this technique is to select samples based on class. The analyrical method used in this study is multiple linier regression analysis with hypothesis testing using the t test and f test. From this study produced answer that have been previously processed that simultaneously effect employee performance and partially effect employee performance.Keywords : Transformasional Leadership Style, Competence, Commitment, Communication and Employee Performance